Poly(ADP-ribose) polymerase inhibitors in prostate and urothelial cancer - Brönimann, Stephan; Lemberger, Ursula; Bruchbacher, Andreas; Shariat, Shahrokh F; Hassler, Melanie R (Current opinion in urology, 2020)
PURPOSE OF REVIEW: The aim of this article is to give an overview of poly(ADP-ribose) polymerase inhibitors (PARPis) trials in prostate cancer and to discuss emerging approaches with potential future clinical implementation in both prostate and urothelial cancer. RECENT FINDINGS: PARPis are a class of drugs that can be applied for the treatment of homologous recombination repair (HRR)-deficient tumors. Tumors are potentially sensitive to PARPi harbor mutations in genes relevant for DNA damage repair, such as BRCA1/2 or ATM, which are present to a significant degree in metastatic prostate and urothelial cancer patients. Several PARPis have been successfully tested in clinical trials for HRR-deficient metastatic castration-resistant prostate cancer (mCRPC), and olaparib and rucaparib have recently received breakthrough approval in BRCA1/2 mutated mCRPC. Combination treatment of PARPis with androgen-receptor inhibitors or with checkpoint inhibitors and earlier frontline applications are currently being evaluated, and clinical trials enrolling bladder cancer (BCa) patients with HRR deficiency have recently been initiated. SUMMARY: Approximately 10% of mCRPC patients and 34% of metastatic BCa patients have tumors with HRR deficiency and may benefit from PARPi treatment. Correct identification of these patients as well as determining the most adequate time point for drug administration will be key to successful clinical implementation.
Keywords: Prostatic Neoplasms; nádory prostaty; Humans; karcinom z přechodných buněk; inhibitory syntézy nukleových kyselin; lidé; PARP inhibitory; Poly(ADP-ribose) Polymerase Inhibitors; Neoplasm Metastasis; metastázy nádorů; Male; nádory močového měchýře; Carcinoma, Transitional Cell; inhibitory enzymů; poškození DNA; DNA Damage; mužské pohlaví; Urinary Bladder Neoplasms; Enzyme Inhibitors; Nucleic Acid Synthesis Inhibitors